Octopus endograft technique in complex aortic pathologies - a retrospective single-center study - Ribeiro,Tiago F. (2023)
Abstract Introduction: Fenestrated/branched EVAR (f/bEVAR) are associated with lower peri-operative major complications, when compared to open repair in complex aortic pathologies. However, f/bEVAR is limited by the waiting time for customized graft production and has specific anatomic limitations. Alternatively, adapting outside instructions-for-use, readily available off-the-shelf devices has been used with variable success. Among these options is the Octopus technique, which consists of parallel stent grafts originating inside a larger external stent graft. Despite being an off-label combination of devices, it can play a role when f/bEVAR is unavailable or inapplicable. Methods: Single center retrospective study, including all consecutive patients treated with the Octopus technique. Baseline characteristics, peri-procedural and follow-up data was obtained. Primary endpoint is clinical success. Secondary endpoints are complications and secondary interventions in follow-up. Results: Between 2015 and February 2022, six patients with a mean of 74±9 years were identified. Treatment indications included three type 1A endoleaks and 3 thoracoabdominal aortic aneurysms (TAAA) without prior intervention, one of which was mycotic. Four procedures were elective and the remaining two emergent. In the elective cases, the Octopus technique was chosen due to anatomical constraints and because waiting time for customization was considered excessive. Excluder and Incraft endografts were used in 5 and 1 cases, respectively. Thirteen visceral branches were revascularized (6 superior mesenteric, 4 renal and 3 celiac arteries). Gutter endoleaks were observed in 2 patients. Mean blood loss, surgery and hospitalization duration was 483 (300) mL, 288 (73) minutes and 26 (19.5) days. One perioperative death occurred, in a patient treated in the context of post-EVAR rupture due to type 1A endoleak. The most frequent postoperative complications were temporary acute renal failure (2/6), paraplegia (2/6) of which one was completely resolved, and non-graft related infection (2/6). One early reintervention, consisting of branch relining due to kinking and gutter embolization was necessary. On follow-up, there were no new endoleaks or endoleak-related interventions. Four patients died within two years, one with an aneurysm-related complication (spondylodiscitis in the context of a mycotic TAAA). The remaining deaths were not aneurysm related. Conclusion: The Octopus technique may offer a valuable off-the-shelf solution for complex aortic diseases, particularly due to anatomical constraints or in the emergent setting. Despite a high technical success rate, there is significant early morbidity and high mid-term mortality. In our series, durability was reasonable for this challenging group of patients, and our outcomes are in accordance with other reports.